The Influence of Brand Ambassador and Brand Image on E-Commerce Purchase Decision at Tokopedia Marketplace (Study on Millennial and Generation Z in Manado) - Jeniffer Gabriella Korompis; Willem J. F. A. Tumbuan; Ferdinand J. Tumewu (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
In the first quarter of 2021, Indonesian e-commerce Tokopedia ranked first among the most clicked e-commerce sites in Indonesia, with around 135 million clicks. There is a shift of purchasing power from generation Z to millennial generation. Millennial and Generation Z are the generation that have grown up tech savvy, living through the evolution of life-changing innovation, such as the launch of the public internet and the smart phone. The popularity of Tokopedia was also driven by a marketing strategy in introducing Tokopedia and its products to the public, one of which is the use of celebrities that attract the public's attention. The using of a brand ambassador is one effective marketing technique to get a lot of attention from the customers. Brand image has an important position in influencing the purchasing decisions by consumers, because one of the the decisions in the structure of the purchasing is the decision regarding the choice of brand The purpose of this study is to know the simultaneous and partial influence of brand ambassador and brand image on consumer purchase decision at Tokopedia marketplace. This research used multiple regression analysis with sample of 100 respondents. The result shows that brand ambassador and brand image have a simultaneous and partial influence on consumer purchase decision at Tokopedia marketplace. Tokopedia should keep BTS and Blackpink as their brand ambassador considering that they’re the most famous Korean boy group and girl group these days and have so many fans especially Millennial and generation Z. Brand image of Tokopedia already good and all Tokopedia need is keep maintaining the corporate image.